Lignocellulosic composition based thermal kinetic study of Mangiferaindica Lam, Artocarpus Heterophyllus Lam and Syzygium Jambolana seeds. (December 2021) - Pal, Dan Bahadur; Srivastava, Neha; Pal, Sunder Lal; Kumar, Mohit; Syed, Asad; Elgorban, Abdallah M.; Singh, Rajeev; Gupta, Vijai Kumar
Graphical abstract: Lignocellulosic Composition Based Thermal Kinetic Study of Mangiferaindica Lam, Artocarpus Heterophyllus Lam and Syzygium Jambolana Seeds. Highlights: Thermochemical characterization of M, JF and JP Seeds kernel biomass. Hemicellulose content in the M, JF and JP were in the range of 6 to 9%. M, JF and JP biomass activation energies value ranged from 179.86 to 226.31 kJ/mol. The maximum value of the pre-exponential coefficient 1.29x10 39 for JP by the FWO. The pre-exponential factor of JP biomass using KAS model was 1.83x10 40 . Abstract: In the present study, pyrolysis of mangifera indica L., Artocarpus heterophyllus L. and jambolana seeds have been performed using thermogravimetric analysis. These biomasses have enriched lignocellulosic composition of hemicellulose (5–10%) and lignin (1–3%) which are unexplored. The TGA analysis was performed at various heating rates of 10, 15, 20, 25 and 30 °C/min from 25 to 600 °C. Kinetic investigation of the pyrolysis method using TGA statistics has been done using iso -conversional models of Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Vyazovkin and Vyazovkin AIC. The apparent activation energies value ranged from 179.86 to 226.31 kJ/mol in the fractional conversion range of 0.1 to 0.7.